The Iliad: An Adventure Classic - Francis, Pauline (Evans Brothers Ltd, 2007)
The story tells of a few days' fighting in the year long war between the Trojans led by King Priam, and the Greeks led by King Agamemnon. Heros from both sides fight one another- how they fight, and how they die, is what is important to them.
Keywords: Juvenile Fiction / Adventure